Influence of Discontinuous PureSperm® and OptiPrepTM Gradient Centrifugations on Bovine Sperm Quality and the Sex Ratio of in vitro Produced Embryos - Kakanang Buranaamnuay (Science Faculty of Chiang Mai University, 2019)
Presently, separation of X- and Y-sperm with flow cytometry is only one successful method of sex selection; however, well-trained personnel and costly instrument are needed for this technique. Therefore, separation with a more simple and convenient method (i.e. a gradient centrifugation) becomes of interest. Influence of 8-layer PureSperm® and OptiPrepTM density gradients on the quality of bovine sperm and the sex ratio of in vitro produced embryos was evaluated. Fresh semen (n=12) with the sperm motility of at least 65% was divided into four aliquots. One aliquot served as a non-centrifuged control sample was frozen in Tris-egg yolk extender. The other three were applied to 8-layer gradients in PureSperm®, OptiPrepTM or Percoll. After centrifugation, the sperm pellet was added with the extender and then frozen. The thawed semen was evaluated for the sperm quality; the sex ratio of sperm was determined in the in vitro produced embryos by multiplex PCR. The viability, acrosome morphology and membrane integrity (HOST) of thawed sperm in the PureSperm® and Percoll groups were similar to the control (p > 0.05) and were significantly higher than those in the OptiPrepTM (p < 0.0001 to p = 0.03). The PureSperm®, OptiPrepTM and Percoll centrifugations did not show a significant increase in X-bearing sperm in the pellet (61.6%, 61.0% and 54.3%, respectively) compared to the control sample (58.8%, p > 0.05). In conclusions, centrifugation of fresh bovine semen in discontinuous 8-layer PureSperm® gradients did not damage the survival of frozen-thawed sperm. However on the basis of testing in the in vitro produced embryos by multiplex PCR, discontinuous PureSperm® and OptiPrepTM gradient centrifugations were not able to deviate the sex ratio of bovine sperm.